Human Polyclonal Antibodies Produced by Transchromosomal Cattle Provide Partial Protection Against Lethal Zaire Ebolavirus Challenge in Rhesus Macaques. (25th July 2018) - Rosenke, Kyle; Bounds, Callie E; Hanley, Patrick W; Saturday, Greg; Sullivan, Eddie; Wu, Hua; Jiao, Jin-an; Feldmann, Heinz; Schmaljohn, Connie; Safronetz, David
Abstract: Antibody therapy has been used to treat a variety of diseases and the success of ZMapp and other monoclonal antibody-based therapies during the 2014–2016 West African Ebola outbreak has shown this countermeasure can be a successful therapy for Ebola hemorrhagic fever. This study utilized transchromosomal bovines (TcB) vaccinated with a DNA plasmid encoding Ebola virus glycoprotein sequence to produce human polyclonal antibodies directed against Ebola virus glycoprotein. When administered 1 day postinfection, these TcB polyclonal antibodies provided partial protection and resulted in a 50% survival rate following a lethal challenge of Ebola virus Makona in rhesus macaques.